The role of political parties in promoting a culture of good governance in Egypt post-2011 - Kandil, Omar (AUC Knowledge Fountain, 2015)
Acknowledging and understanding the opportunities in Egypt post-2011, this research focuses on Egyptian political parties, and their potential role in Egypt’s ongoing transition, instigated by the events of January 2011. The main purpose of this paper was to answer the research question which is centered around the extent to which political parties can promote a culture of good governance in Egypt post-2011, taking several major parties and events as cases for the analysis. The main objectives of this research were to thoroughly understand the context in which political parties developed in Egypt and analyze the major recognized components of good governance, in order to ultimately assess how newly established political in parties in Egypt can contribute to the promotion of these components in post-2011 Egypt. This allowed to view these parties more in depth and properly assess their role in Egypt’s current transition in relation to extrapolated components of good governance such as transparency, accountability, capacity building, rule of law , participation and representation, effectiveness, among other elements. It also provided insights on the potential opportunities for these institutions in Egypt, in terms of what they can bring to the transition if empowered and nurtured. Qualitative interviews were undertaken with party officials along with content and discourse analysis in order to provide holistic perceptions of the subject of study. The findings of the analyzed data allowed to provide insights on internal mechanisms of political parties which demonstrate elements of good governance. Various intra-party mechanisms showcased several aspects of commitment to transparency, accountability, capacity building, participation and this was the case for parties in various areas of the political spectrum. It also granted the research with an understanding of Egyptian parties in the context of elections, including processes of pre-elections such as internal and external endorsements of candidates as well as various alliances formations and formulation of party programs and platforms. Multi-party collaboration has also been a focal element of the analysis, with a focus on the stances and formal positions of various parties in regards to legislations and other macro-issues affecting the Egyptian political scene. Policy recommendations conclude the paper and allow for the research to serve as a comprehensive framework for understanding the potential role of political parties in Egypt post-2011 and what opportunities can allow for stronger parties to have a more significant role in promoting good governance in Egypt’s ongoing transition moving forward.